Skelepun25
Answered

Which quadratic equation is equivalent to (x + 2)^2 + 5(x + 2) – 6 = 0? A. (u + 2)^2 + 5(u + 2) – 6 = 0 where u = (x – 2) B. u^2 + 4 + 5u – 6 = 0 where u = (x – 2) C. u^2 + 5u – 6 = 0 where u = (x + 2) D. u^2 + u – 6 = 0 where u = (x + 2) (This is a question from Edg by the way)

Answer :

Answer:

C. u^2 + 5u – 6 = 0 where u = (x + 2)

Step-by-step explanation:

(x + 2)^2 + 5(x + 2) – 6 = 0

Let u = x+2

(u)^2 + 5(u) – 6 = 0

Answer:

C.u^2+5u-6=0

Step-by-step explanation:

By comparing (x+2)^2+5(x+2)-6=0 to answer C,that is u^2+5u-6=0,u=(x+2).

By sustituting (x+2)into answer C,we get;

(x+2)^2+5(x+2)-6=0 which is the same as the quadriatic equation given in the question.

Other Questions